2017
DOI: 10.1093/ptj/pzx086
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk of Inappropriate Sexual Behavior of Patients Toward Physical Therapist Clinicians and Students in the United States

Abstract: The extremely high prevalence of IPSB among physical therapist professionals warrants practitioner and student education as well as clear workplace policy and support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…Through 108 questionnaires from clinical and non-clinical medical staff at Hospital Kuala Lumpur (HKL), it is found that over 40% of them are exposed to sexually-related misbehaviour from patients. Contradicting with Boissonnault et al (2017), the results from Yusop, Dempster, and Stevenson (2014) unveiled that occurrence of harassment does not differ between employees' grade and position. Yusop et al (2014) also found that harassment, which also constitutes sexual, is topmost experience inappropriate followed by bullying and mobbing.…”
Section: An Overview Of Sexual Harassment On Medical Practitioners Inmentioning
confidence: 89%
See 3 more Smart Citations
“…Through 108 questionnaires from clinical and non-clinical medical staff at Hospital Kuala Lumpur (HKL), it is found that over 40% of them are exposed to sexually-related misbehaviour from patients. Contradicting with Boissonnault et al (2017), the results from Yusop, Dempster, and Stevenson (2014) unveiled that occurrence of harassment does not differ between employees' grade and position. Yusop et al (2014) also found that harassment, which also constitutes sexual, is topmost experience inappropriate followed by bullying and mobbing.…”
Section: An Overview Of Sexual Harassment On Medical Practitioners Inmentioning
confidence: 89%
“…Meanwhile, the second criteria that were unravelled were medical practitioners' personal and professional characteristics which considered age, gender, marital status, treatment types and experience in providing care. Hence, Boissonnault et al (2017) unveiled that young and single female therapists with less working experience are prone to experiencing the inappropriate behaviour towards them. The final criteria for explaining sexual harassment is the specific abusive actions or events.…”
Section: An Overview Of Sexual Harassment On Medical Practitioners Inmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 ISB can be experienced by both healthcare professionals and patients, and can affect both professionals and patients in many areas. 10 However, studies on the subject generally include case reports or small case series, 11 and most of the research has been conducted on patients who have dementia and/or who are elderly people 12 ; the literature is therefore limited. 13 In this context, this review was written to investigate ISB and to study the responsibilities of nurses in the management of ISB in line with the literature.…”
Section: Introductionmentioning
confidence: 99%